Sobre as decisões monocráticas nos tribunais: o manejo dos agravos interno e regimental - Guimarães, Rafael de Oliveira (2008)
This search is committed to study about decisions made by only one judge on the superior courts, specially relating to their unappealable effects, which is been introduced to the procedure brazilian law by the amended judicial legislation reforms, as seen in the clause number 527, sole paragraph of Civil Procedure Code. Thus, it is clear a discussion among law principles such as the right of appeal and collegiate court versus the procedure economy and celerity. This is because, objecting to empty the Brazilian Courts, for many times, the reforms block the proper right of appeal and also interrupt any urgent guardianship, which should be given in the beginning of the appeal; as unpredictable consequence, it is remarkable an increasing of others procedure remedies, such as the writs of error coram nobis. For that, the present search, initially, talks about principles governing proceedings in the Courts, followed by analise the power of a decision made by the court judge committed to decide primarily the judicial demand, before going to the collegiate, and finally, give clearly the proper remedies available to contest such decisions, reknown as Internal Interlocutory Appeal and Regimental Interlocutory Appeal, and others